Roughness parameter selection for novel manufacturing processes. Issue 1 (4th March 2013) - Ham, M.; Powers, B. M.; Brown, Christopher A.
Summary This work proposes a method of roughness parameter (RP) selection for novel manufacturing processes or processes where little knowledge exists about which RPs are important. The method selects a single parameter to represent a group of highly correlated parameters. Single point incremental forming (SPIF) is used as the case study for the manufacturing process. This methodology was successful in reducing the number of RPs investigated from 18 to 8 in the case study. SCANNING 36:21–29, 2014. © 2013 Wiley Periodicals, Inc.